2022
DOI: 10.1177/21674795221116884
|View full text |Cite
|
Sign up to set email alerts
|

Media Framings of the Transgender Athlete as “Legitimate Controversy”: The Case of Laurel Hubbard at the Tokyo Olympics

Abstract: In this paper, we draw upon Hallin’s typology of journalistic writing to examine the role of the media in framing transgender participation in sport as a ‘legitimate controversy’, and thus up for public debate. Focusing on the media coverage before, during and after New Zealand weightlifter Laurel Hubbard’s debut at the 2020 Tokyo Olympics, we reveal three key strategies used by journalists to frame the topic in polarizing terms: i) sourcing practices, ii) use of science, and iii) questioning of policy. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This master narrative also coincides with larger societal discourses of transmisogyny (Arayasirikul & Wilson, 2019) such that transfeminine athletes told stories about the stigma and rhetoric of sport advantage by participating on women’s sports teams, which inhibited their ability to participate and reinforces binary structures. These stories highlight how specific feminist perspectives rooted in gender binary master narratives about inclusion versus fairness (Scovel et al, 2022) can underpin a transphobic responses (Caudwell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This master narrative also coincides with larger societal discourses of transmisogyny (Arayasirikul & Wilson, 2019) such that transfeminine athletes told stories about the stigma and rhetoric of sport advantage by participating on women’s sports teams, which inhibited their ability to participate and reinforces binary structures. These stories highlight how specific feminist perspectives rooted in gender binary master narratives about inclusion versus fairness (Scovel et al, 2022) can underpin a transphobic responses (Caudwell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in 2021, weightlifter Laurel Hubbard became the first openly trans woman to compete in an Olympics Game and was subjected to online abuse and media hounding. 16 Trans men athletes have typically been the subject of less public debate; however, Chris Mosier, known for being the first trans man to compete in a men's Olympic Trials in 2020, has spoken openly about the challenges faced to be eligible for these competitions. 17,18 The increased visibility of trans people, in general, has fuelled ongoing public debates and policy actions around the inclusion of trans people in sport.…”
Section: Brief View Of Transgender Participation In Sportmentioning
confidence: 99%
“…For instance, Pew Research found that in a national poll of 10,188 randomly sampled adults in the United States, Republicans were over 45% more likely than Democrats to favor requiring trans people to play on sports teams and use restrooms associated with their assigned sex at birth (Parker et al., 2022). Consequently, hundreds of thousands of dollars have been allocated to anti‐trans digital advertisements, resulting in the widespread dissemination of anti‐trans rhetoric (Petrovic, 2023), which presumably shapes public opinion about anti‐trans legislation (Scovel et al., 2022).…”
Section: Introductionmentioning
confidence: 99%